PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN SIKAP TOLERANSI SISWA DI SMPN 2 DONGGO - Fajira, Era; Abdul Fattah; Wahdaniya (Almeera Education, 2024)
This study aims to determine the role of Islamic education teachers in building students' tolerance attitudes, and to determine the description of students' tolerance attitudes, as well as to determine the supporting and inhibiting factors of Islamic education teachers in building students' tolerance attitudes at SMPN 2 Donggo, Bima Regency. This study uses a Qualitative Method with a qualitative descriptive type, namely focusing on understanding the phenomena that occur in the field. The data collection techniques use observation, interview and documentation techniques. The results of the study indicate that the role of Islamic education teachers in building tolerance attitudes at SMPN 2 Donggo, namely by providing guidance, direction, advice, giving good examples, and motivating students so that they understand the importance of appreciating and respecting existing differences, such as differences in beliefs, ethnicity, race, language and background. at SMPN 2 Donggo has several descriptions of students' tolerance attitudes, namely by respecting and respecting each other. There are two supporting factors for teachers in building tolerance attitudes, namely parents and the social environment. While the inhibiting factors are a curriculum that is too theoretical, the inability of teachers to deal with differences of opinion, and the lack of supporting resources.